Foreign investment disputes : cases, materials and commentary - Bishop, R. Doak (Kluwer Law International The HagueNL, 2005)
Covers all aspects of foreign investment disputes viz. the treaty system protecting investments; investment contracts and key clauses; forums for resolving investment disputes; political risk insurance; applicable law; principles of state responsibility; investor rights under investment treaties and customary international law; defenses to investor claims; reparations; procedure and proof; and, enforcement of arbitral awards.